Analysis of Factors That Affects the Capital Structure within Companies Included in the Index of LQ45 during 2011 - 2013 - Dominica Rufina; Stefanus Ariyanto; Theresia Lesmana (Binus Business Review, 2015)
This study aims to determine the factors of ROA, Asset Structure, Sales Growth, and Firm Size affecting Capital Structure. The population in this study is the companies included in the Index LQ45 Indonesia Stock Exchange from the period 2011 to 2013, the data of a total of 270 listed companies in LQ45 during that period, only 90 corporate data that successively included in the index LQ45. The data used in this study uses secondary data from the Indonesia Stock Exchange website www.idx.co.id. In the process of data analysis and testing the assumptions of classical hypothesis testing using multiple linear regression analysis using SPSS v20.00. The results showed that partially variable ROA, Asset Structure, and Firm Size has a significant influence on the Capital Structure, Growth Sales whereas variable has no influence on the Capital Structure. Simultaneously ROA, Asset Structure, Sales Growth, and Firm Size effect on Capital Structure.